Land Titling: A Sine Qua Non For Enhancing Property Taxation - Akinlabi, Akintomide Joseph; Ige, Victor Olutope (International Journal of Engineering and Management Research, 2019)
The use of property tax to salvage the recurrent financial insolvency of government at all levels in Nigeria have achieved little success over the years. Concerted efforts to improve this situation have achieved little success. This study therefore investigates the potential of titling at enhancing property taxation in Akure, Ondo State, Nigeria. Data was obtained from the purposive selected areas of Akure and the Ondo State Ministry of Lands and Housing as well as the Ondo State Board of Internal Revenue. Data analysis reveals that 85.5 percent of the residents are without title to their land, while only 11.86 percent of the residents who titled their land paid their ground rents up to date. The difference in the means of the ground rent paid as a form of property tax by residents with titled land and the ground rent anticipated from residents without title to their land is statistically significant at 0.001. Stringent requirements, poor service delivery as well as lack of sensitization on guidelines and procedures to follow are major constraints to titling in the study area. There was a strong negative correlation between titling and property tax. Capacity building in systematic titling project is a worthwhile policy option for improved titling culture in the study area.